Modeling and intellectual development in first grade students - Guerra Vento , M. Sc. Vilma; Rivero Rivero , Dra. C. Melva Luisa; Cuenca Díaz , Dra. C. Maritza (Transformación, 2024)
This paper is aimed at explaining how first grade students are capable of assimilating modeling as a procedure for foretelling the results of actions in progress. The study was carried out by means of a controlled experiment introducing a methodology that favors the intellectual development of first year children by means of story modeling. The assimilation of the procedures —comprehension and text construction— was found to be helpful not only for planning actions but for cognitive and affective development as well.